Development of an Infusion for LDL Cholesterol Based on Avocado Leaves (Persea americana), Guava Leaves (Psidium guajava) and Cinnamon - Revelo-Cáceres, Daniel; Oliveras-López, María Jesús; López-García de la Serrana, Herminia (European Journal of Applied Sciences, 2023)
An infusion based on avocado leaves, guava leaves and cinnamon was developed as a potential alternative for the treatment of LDL cholesterol. Avocado and guava leaves were washed, dehydrated and ground. Optimal dehydration length for avocado leaves was determined using weight loss curves, from which it was decided to treat leaves for 60 minutes at 40ºC. Similarly, optimal dehydration conditions for guava leaves were achieved in a period of 80 minutes at 45ºC. Three infusion formulations were tested. All formulations contained 1.5 g of guava leaves and 6 g of cinnamon, alongside 5, 10 and 15 g of dehydrated avocado leaves, respectively. A sensory analysis was carried out in which raters ranked the infusions in terms of taste and aroma, Basker's preference test was conducted and purchase intentions were gaged. Tasters preferred the formulation containing the lowest amount of dehydrated avocado leaves. 91.67% of tasters indicated that they would buy this infusion due to its possible functional properties.